2012
DOI: 10.33549/physiolres.932379
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Analysis of Normal and Abnormal Chick Ventricular Myocardial Development

Abstract: The left and right ventricle originate from distinct parts of the cardiac tube, and several genes are known to be differentially expressed in these compartments. The aims of this study were to determine developmental differences in gene expression between the left and right ventricle, and to assess the effect of altered hemodynamic loading. RNA was extracted from isolated left and right normal chick embryonic ventricles at embryonic day 6, 8, and 10, and from day 8 left atrial ligated hearts with hypoplastic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Since LAL is a side specific surgery mainly affecting the left side of the heart, it was reported that it alters hemodynamics in a side-specific manner [25]. Krejčí et al conducted a study which unraveled differential gene expression between control and LAL hearts at ED8 [45]. The microarray analyses identified 91 genes that were differently expressed between control and LAL hearts, while only 66 were different between right ventricles and left ventricles.…”
Section: Lal Induced Pathway Alterationsmentioning
confidence: 99%
“…Since LAL is a side specific surgery mainly affecting the left side of the heart, it was reported that it alters hemodynamics in a side-specific manner [25]. Krejčí et al conducted a study which unraveled differential gene expression between control and LAL hearts at ED8 [45]. The microarray analyses identified 91 genes that were differently expressed between control and LAL hearts, while only 66 were different between right ventricles and left ventricles.…”
Section: Lal Induced Pathway Alterationsmentioning
confidence: 99%
“…A previous study have also attempted to characterize the gene expressions in the LV after LAL through microarray analysis, to assist in pinpointing the mechanobiological pathways that may be causing LV hypoplasia [ 22 ]. A total of 91 differentially express genes in the LV and 66 gene in the right ventricle were reported.…”
Section: Introductionmentioning
confidence: 99%